ACTUAL ISSUES OF DIAGNOSIS OF DEEP INFILTRATIVE ENDOMETRIOSIS - Сергей Владимирович Баринов; Оксана Вячеславовна Лазарева; Юрий Тимофеевич Игнатьев; Владимир Леонидович Полуэктов; Сергей Игоревич Мозговой; Владимир Владимирович Полуэктов; Людмила Леонидовна Шкабарня; Юлия Игоревна Тирская (The Publishing House Medicine and Enlightenment, 2020)
The purpose of the study is to determine the prognostic value of clinical data, ultrasonography, magnetic resonance imaging (MRI), colonoscopy for the diagnosis of deep infiltrative endometriosis (DIE). Materials and methods. The study included 139 patients with external genital endometriosis, 68 of whom confirmed DIE. The comparison group consisted of 71 women without signs of DIE. Conducted general clinical, ultrasound, MRI of the pelvis, colonoscopy, biopsy of the mucous membrane of the rectum. All patients underwent surgical treatment followed by a morphological examination. Statistical analysis was performed using the statistical package Statistica 7.0. The χ² indicator was considered (p <0.05 was considered statistically significant). Non-parametric Mann-Whitney test, sensitivity, specificity, the prognostic value of positive and negative results, likelihood ratio of positive and negative results. Laparoscopy and pathologic indicators were the «gold standard» for diagnosis anatomical research. Results. There were no significant differences in clinical symptoms between patients. The sensitivity and specificity of the bimanual study to detect infiltration were 89.7 % and 84.5 %, respectively. The sensitivity and specificity of ultrasound in the diagnosis of DIE - 91.8 % and 98.2 %, MRI - 85.15 % and 93.75 %, respectively. In 73.3 % of cases, a colonoscopy revealed the deformation of the anterior wall of the rectum in the projection of the infiltration location. According to the rectal biopsy in three cases out of fifteen revealed «focal endometriosis». Application. Obstetrics and gynecology. Summary. This study allows determines the location and amount of infiltration; to assess the degree of involvement in the pathological process of nearby organs, which is necessary for the formation of a multidisciplinary surgical team and prepare the necessary equipment, and develop a perioperative plan of patients.